Response to a Comment on "Malignant transformation evidences of Oral Lichen Planus: When the time is of the essence". (February 2022) - Zotti, Francesca; Nocini, Riccardo; Capocasale, Giorgia; Fior, Andrea; Peretti, Martina; Albanese, Massimo
Highlights: To replay to Desai R.S Oral Oncol 2021; 105080 . This comment can help in customized follow-up. To provide clarification about the risk factors of OLP malignant transformation.